THE EFFECT OF FINANCIAL LITERACY ON FINANCIAL SATISFACTION THROUGH FINANCIAL BEHAVIOR AS AN INTERVENING VARIABLE ON MILLENNIAL GENERATION IN BEKASI CITY - Siti Aisyah; Muhammad Richo Rianto; Eri Bukhari (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to measure the direct effect and indirect effect of financial literacy on financial satisfaction by using financial behavior as an intervening variable in the millennial generation in Bekasi City. The results of this study provide an explanation that the financial literacy variable has a positive and significant effect on financial behavior, financial behavior has a positive and significant effect on financial satisfaction, and financial behavior is able to mediate the indirect effect of financial literacy on financial satisfaction. However, the direct effect of financial literacy has no effect on financial satisfaction, in this study it shows that financial satisfaction is not affected by the high level of financial literacy.